2019
DOI: 10.1080/14712598.2019.1622678
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of secukinumab in Italian patients with psoriasis: an 84 week, multicenter, retrospective real-world study

Abstract: Background: Long term data on the real-life use of secukinumab are scant. The aim of this study was to investigate the real-life effectiveness, safety and treatment persistence of secukinumab in patients with moderate-to-severe psoriasis. Research design and methods: This 84-week, multicenter (n = 7) retrospective study analyzed data from patients who initiated and received at least 6 months of secukinumab treatment between June 2016 and June 2018 in the Campania region of Italy. Patient demographic and treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
52
4
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(69 citation statements)
references
References 32 publications
(55 reference statements)
12
52
4
1
Order By: Relevance
“…Indeed, in this best-responder patient subcohort, BMI was slightly lower (26.0 vs. kg/m 2 ), disease duration was shorter, arthritis was less observed, age was slightly lower, compared to bioexperienced ( Table 2). This is in line with other reports, showing a greater and faster response to secukinumab in patients bio-naïve, younger, and with lower BMI (11,12,15). Notably, in this study, treatment response in bio-naïve patients was higher compared to bio-experienced patients who showed lower response rates, notwithstanding a higher proportion of patients with baseline PASI score 20.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Indeed, in this best-responder patient subcohort, BMI was slightly lower (26.0 vs. kg/m 2 ), disease duration was shorter, arthritis was less observed, age was slightly lower, compared to bioexperienced ( Table 2). This is in line with other reports, showing a greater and faster response to secukinumab in patients bio-naïve, younger, and with lower BMI (11,12,15). Notably, in this study, treatment response in bio-naïve patients was higher compared to bio-experienced patients who showed lower response rates, notwithstanding a higher proportion of patients with baseline PASI score 20.…”
Section: Discussionsupporting
confidence: 92%
“…Although secukinumab has been shown to be well tolerated and effective in treating patients with plaque psoriasis and PsA in multiple clinical trials (7-9,29-34) with up to 5-year follow up (35), randomized controlled trials are likely to enroll patient populations with more stringent inclusion/exclusion criteria and generally the study design allows a short-term observation compared to the real-world setting. A variety of real-world studies have been recently published: some of them analyzed secukinumab drug survival (36)(37)(38)(39), whereas others assessed its efficacy in psoriasis patient populations with peculiar features, or assessing its effectiveness as improvement of DLQI, BSA, PGA, and PASI scores (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Nevertheless, they reported favorable secukinumab safety and effectiveness in terms of mean reduction of PASI value over time, as patient rates achieving PASI 75, PASI 90, and PASI 100 responses at different timepoints, Investigator's Global Assessments or improvements in quality of life measures (11)(12)(13)(14)(15)(16)(17)(18)(19)22).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with treated LTBI were not excluded from four phase 2, six phase 3, and two phase 4 secukinumab clinical trials [38], and no cases of TB activation were reported. In a multicenter study of 324 patients with moderate to severe psoriasis treated with secukinumab including ten patients with LTBI treated, secukinumab was effective and safe, with only one case of LTBI reported [39]. In 2044 patients with moderate to severe PsO treated with secukinumab, no cases of TB were observed after 1 year of treatment.…”
Section: Chronic Illnessesmentioning
confidence: 99%